Integration of Cash Waqf and Waqf Through Cash in Islamic Social Finance: Opportunities, Challenges, and Policy Implication - Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
The integration of cash waqf and waqf through money offers an innovative approach to strengthening Islamic social finance by expanding the donor base, enhancing instrument flexibility, and optimizing the productive use of waqf assets. However, the absence of a uniform legal framework, low public literacy, and limited nazhir capacity continue to pose significant challenges. This study employs a qualitative design using a systematic literature review of 62 international publications indexed in Scopus, WoS, and Google Scholar. The findings indicate that integrating both waqf models can enhance the inclusivity of social funding and strengthen economic empowerment when supported by professional governance, adaptive regulation, and digital innovation. The study concludes that policy harmonization, nazhir capacity building, and the strengthening of the waqf literacy ecosystem are essential prerequisites for effective implementation.